Proteomic studies on gastric cancer to understand the underlying molecular mechanisms of oncogenesis - Guo, Tiannan (2012)
Gastric cancer ranks as the fourth most common cancer and the second leading cause of cancer mortality globally. One of the main reasons for gastric cancers’ poor outlook is the limited knowledge of the underlying molecular mechanisms of gastric oncogenesis. Proteomics has evolved rapidly in recent years and is now recognised as a powerful suite of tools to systematically dissect molecular abnormalities in cancer cells. However, proteomics has yet to be intensively applied to gastric cancer; consequently few global insights into gastric oncogenesis to date have emerged from this approach. In this thesis, we employed advanced proteomic techniques to study phosphorylated proteins, methylated proteins, and cell surface proteins of multiple gastric cancer cells on a large scale. Proteomic data were correlated with transcriptome data sets to gain deeper insights into aberrantly expressed proteins in gastric cancer cells. We found MET, a receptor tyrosine kinase, to be a dominant aberrant protein that was overexpressed in some gastric cancers. A quantitative proteomic approach was utilized to investigate molecular events associated with MET-directed therapy in gastric cancer cells. Remarkably MET was found to be present in the mitochondria of gastric cancer cells, as it was on the plasma membrane. Moreover, mitochondrial MET was identified as a direct target of the MET kinase inhibitor, PHA-665752. Taken together, data presented in this thesis offer a systematic and unbiased profile of multiple molecular abnormalities in gastric cancer cells, and has uncovered a novel mechanism of action of molecularly-directed cancer therapy.